Sexual Harassment against Female Nurses at Hospitals in Jakarta, Indonesia - Muhammad Irfan Syaebani; Wahyu Muhamad Zen; Monica Devina; Uliyatun Nikmah; Dindha Vitri Primadini (Pusat Studi gender dan Anak (PSGA) Universitas Islam Negeri Walisongo Semarang, 2022)
Sexual harassment of female employees in the workplace is a pervasive problem, especially in hospitals that rely on nurses to deliver medical care through physical contact with several patients, therefore increasing their risk of sexual harassment. The purpose of this study is to examine the circumstances and experiences of sexual harassment against female hospital nurses in Jakarta, Indonesia. The research employed a qualitative, phenomenological approach, with eight informants participating in In-Depth Interviews and coding analysis. According to the subjects of the study, sexual harassment happened during work hours, making them victims. Sexual harassment can range from subtle to overt, from gestures to physical assault. The majority of perpetrators are male. While female nurses are providing medical treatment, visiting patients, or engaging in training, sexual harassment may occur. The findings point to preventative strategies such as policy development, training, and increasing public awareness of sexual harassment, as well as a coping strategy that involves assisting victims in reporting their experiences through an established grievance procedure system to reach a fair resolution.